RELATIONSHIP BETWEEN CORAL REEF COVER CONDITION AND MEGABENTHOS ABUNDANCE IN PASUMPAHAN ISLAND, WEST SUMATRA - Manik, Pilipus Fiter; Thamrin, Thamrin; Mubarak, Mubarak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This study analyzes live coral cover, megabenthos abundance, and the relationship between coral reef condition and megabenthos abundance in Pasumpahan Island waters. The survey method was used to collect primary and secondary data. The results showed that the average percentage of live coral reef cover in Pasumpahan Island, West Sumatra, was 33.31%. The abundance of megabenthos obtained was 10,000 ind/ha. Regression results showed a strong positive correlation between coral reef cover and megabenthos abundance, with an R2 value of 0.5396, meaning that the percentage of live coral affects megabenthos by 53.96%.